2018
DOI: 10.5604/01.3001.0012.0933
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of Vascular Involvement in Egyptian Patients with Budd-Chiari Syndrome: Relation to Etiology and Impact on Clinical Presentation

Abstract: Isolated HVs occlusion was the most common pattern of vascular involvement in Egyptian patients with primary BCS. Vascular pattern of involvement affected the clinical presentation and was related to the underlying thrombophilia in those patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
0
3
1
Order By: Relevance
“…Previous studies found that BCS was usually occurring during the third or fourth decade of life, with slightly more common predominance in females. 10 Another study in Egypt describing disease pattern in Delta region and Cairo found more females affection than males with M/F ratio 43/57 and mean patient age about 28 years, 11 while our study showed that BCS is mainly occurring at middle age with the mean age about 32 years with male predominance: M/F 28/22. AN Algerian study found that M/F was 45/70 and the mean age was 34 years.…”
Section: Discussioncontrasting
confidence: 43%
See 2 more Smart Citations
“…Previous studies found that BCS was usually occurring during the third or fourth decade of life, with slightly more common predominance in females. 10 Another study in Egypt describing disease pattern in Delta region and Cairo found more females affection than males with M/F ratio 43/57 and mean patient age about 28 years, 11 while our study showed that BCS is mainly occurring at middle age with the mean age about 32 years with male predominance: M/F 28/22. AN Algerian study found that M/F was 45/70 and the mean age was 34 years.…”
Section: Discussioncontrasting
confidence: 43%
“…31 This study showed that HVs obstruction was the most common pattern of venous obstruction (80%), combined HVs and IVC obstruction was similar to isolated IVC obstruction and were observed in 10%, while in another Egyptian study by Sakr et al, HVs obstruction, IVC obstruction, and combined HVs and IVC obstruction were found in 43%, 3%, and 21% of patients, respectively. 11 Darwish Murad reported isolated obstruction of HV, IVC, and both veins in 62%, 7%, and 31% of patients, respectively. Behcet's disease was the main etiology associated with IVC obstruction in this study.…”
Section: Dovepressmentioning
confidence: 98%
See 1 more Smart Citation
“… 4 6 We, however, showed in our patient that the venous obstruction was noted in both the HV and the IVC. Combined HV and IVC obstruction was found in 10% and 21% of BCS patients in studies conducted in Egypt by Ahmed et al 15 and Sakr et al, 16 respectively. Darwish Murad et al 17 in their study of patients treated at tertiary hospitals in France and the Netherlands found that 31% of patients with BCS had combined HV and IVC obstruction.…”
Section: Discussionmentioning
confidence: 92%